Femtosecond pulse operation of a Tm,Ho-codoped crystalline laser near 2 μm - Lagatsky, A. A.; Fusari, F.; Calvez, S.; Kurilchik, S. V.; Kisel, V. E.; Kuleshov, N. V.; Dawson, M. D.; Brown, C. T. A.; Sibbett, W. (Optical Society of America, 2010)
We demonstrate, for the first time to our knowledge, femtosecond-regime mode locking of a Tm,Ho-codoped crystalline laser operating in the 2 μm spectral region. Transform-limited 570 fs pulses were generated at 2055 nm by a Tm,Ho:KY(WO4)2 laser that produced an average output power of 130 mW at a pulse repetition frequency of 118 MHz. Mode locking was achieved using an ion-implanted InGaAsSb quantum-well-based semiconductor saturable absorber mirror.